Low serum lymphocyte level is associated with poor exercise capacity and quality of life in chronic obstructive pulmonary disease - Moon, Sung Woo (Sci Rep, 2020)
The purpose of this study was to evaluate the association of serum lymphocyte level with several clinical parameters in COPD. The study population included 451 COPD patients from the Korean Obstructive Lung Disease cohort study. Serum lymphocyte level was measured every year along with various clinical parameters, such as lung function, 6-min walking (6 MW) distance, quality of life using COPD assessment test (CAT) and St. George's Respiratory Questionnaire (SGRQ) scores, exacerbations, and survival. Serum lymphocyte level less than 20% was considered as a low lymphocyte level. Normal lymphocyte and low lymphocyte groups comprised of 409 (90.7%) and 42 (9.3%) patients, respectively. Clustered analysis showed that patients in low lymphocyte group had a lower post-bronchodilator forced expiratory volume in 1 s % predicted (estimated mean =  − 5.70%; P = 0.001), a lower forced vital capacity % predicted (estimated mean =  − 5.63%; P = 0.005), a shorter 6 MW distance (estimated mean =  − 41.31 m; P < 0.001), a higher CAT score (estimated mean = 2.62; P = 0.013), and a higher SGRQ score (estimated mean = 10.10; P < 0.001). Serum lymphocyte level was not associated with frequent acute exacerbations nor mortality. Low serum lymphocyte group showed poorer pulmonary function, lower 6 MW distance, and worse quality of life. Serum lymphocyte levels could be a simple and widely available predictive marker for variable clinical outcomes in COPD patients.